Morphology of blood microbiota in healthy individuals assessed by light and electron microscopy - Tsafarova, Borislava; Hodzhev, Yordan; Yordanov, Georgi; Tolchkov, Vladimir; Kalfin, Reni; Panaiotov, Stefan (Frontiers in Cellular and Infection Microbiology, 2023)
The blood microbiome is still an enigma. The existence of blood microbiota in clinically healthy individuals was proven during the last 50 years. Indirect evidence from radiometric analysis suggested the existence of living microbial forms in erythrocytes. Recently targeted nucleic acid sequencing demonstrated rich microbial biodiversity in the blood of clinically healthy individuals. The morphology and proliferation cycle of blood microbiota in peripheral blood mononuclear cells (PBMC) isolated from freshly drawn and cultured whole blood are obscure. To study the life cycle of blood microbiota we focused on light, and electron microscopy analysis. Peripheral blood mononuclear cells isolated from freshly drawn blood and stress-cultured lysed whole blood at 43 ○C in presence of vitamin K from healthy individuals were studied. Here, we demonstrated that free circulating microbiota in the PMBC fraction possess a well-defined cell wall and proliferate by budding or through a mechanism similar to the extrusion of progeny bodies. By contrast, stress-cultured lysed whole blood microbiota proliferated as cell-wall deficient microbiota by forming electron-dense or electron-transparent bodies. The electron-dense bodies proliferated by fission or produce in chains Gram-negatively stained progeny cells or enlarged and burst to release progeny cells of 180 – 200 nm size. On the other hand, electron-transparent bodies enlarged and emitted progeny cells through the membrane. A novel proliferation mechanism of blood microbiota called by us “a cell within a cell” was observed. It combines proliferation of progeny cells within a progeny cell which is growing within the “mother” cell. The rich biodiversity of eukaryotic and prokaryotic microbiota identified in blood by next-generation sequencing technologies and our microscopy results suggest different proliferation mechanisms in whole and cultured blood. Our documented evidence and conclusions provide a more comprehensive view of the existence of normal blood microbiota in healthy individuals.